Paraconsistency and Sette’s calculus P1 - Ciuciura, Janusz (Logic and Logical Philosophy, 2015)
In 1973, Sette presented a calculus, called P1, which is recognized as one of the most remarkable paraconsistent systems. The aim of this paper is to propose a new axiomatization of P1. The axiom schemata are chosen to show that P1 behaves in a paraconsistent way only at the atomic level, i.e. the rule: α, ~α / β holds in P1 only if α is not a propositional variable.